Beyond universal models a dual-pathway conceptual framework for fintech adoption in multi-ethnic emerging economies - Faiz, Azizul; Fernando, Yudi; Faris, Azizul (HBZ & Partners PLT, 2025)
Standard theories on Financial Technology (Fintech) adoption assume a single decision-making process and overlook deep institutional factors present in diverse economies. This paper introduces a dual-pathway conceptual framework derived from studies of Malaysian Micro, Small, and Medium Enterprises (MSMEs). Studies identified two different adoption routes for entrepreneurs from diverse backgrounds that are shaped by national socio-economic policies. Non-Bumiputera entrepreneurs follow a Pragmatic-Utilitarian Pathway and Bumiputera entrepreneurs follow an Experiential-Hedonic Pathway. The framework provides guidance for stakeholders and suggests a need for tailored strategies instead of a uniform approach to financial inclusion.